Indicadores de gobernanza territorial de los objetivos del Plan Nacional del Buen Vivir (PNBV 2013-2017), Ecuador. (2018)
The purpose of this article is to analyze the variables and their indicators of territorial governance contained on National Secretariat of Planning and Development Report: “Objectives and indicators of support for the National Plan for Good Living 2013-2017”. Using Whittingham’s taxonomy, there are 37 indicators of territorial governance (25 %), distributed in: efficiency 65%, equity 13.5%, participation 10.8%, accountability 8 % and, human resource development 2.7%; there is omission of important indicators in all these variables, lack of training for the public servant, underestimation of processes of accountability and representation of interest groups, as well as neglect of the institutional mechanisms of citizen participation, revealing a focused governance model in the state. At the regional level, there were improvements in most of the indicators, but stagnation in the field of higher education, committing future processes of generation and transfer of innovations, which are keys for development.